2018
DOI: 10.4103/njcp.njcp_316_17
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and distribution of cancers in Akwa Ibom State, Nigeria

Abstract: There is a variation between the pattern of cancer in Akwa Ibom and other regions of Nigeria warranting further clinicopathological evaluation, and these results will be useful in the overall context of planning and evaluation of cancer control activities in Akwa Ibom State. A population-based cancer registration in Uyo is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 1 publication
6
16
0
Order By: Relevance
“…Cancer occurs in a relatively younger average age range in the rest of Cross River State 49.18 ± 18.9, this compares with the Calabar data where Ekanem and Parkin reported 43.6 in females and 52.3 in males [1]. This pattern is commonly reported in many Nigerian studies [16,[24][25][26] and some African studies as well as among Blacks in the diaspora [27,28]. It has been argued that African populations are generally young and this is reflected in the mean populations affected by non-communicable diseases such as cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Cancer occurs in a relatively younger average age range in the rest of Cross River State 49.18 ± 18.9, this compares with the Calabar data where Ekanem and Parkin reported 43.6 in females and 52.3 in males [1]. This pattern is commonly reported in many Nigerian studies [16,[24][25][26] and some African studies as well as among Blacks in the diaspora [27,28]. It has been argued that African populations are generally young and this is reflected in the mean populations affected by non-communicable diseases such as cancer.…”
Section: Discussionsupporting
confidence: 74%
“…In some European countries and United State of America, the most common cancer in both genders is lung, breast, prostate, colorectum and urinary bladder while in West Asia and North Africa, the lung, breast, colorectum, urinary bladder, and stomach topped the list [19]. In Nigerian studies, the heterogeneity in cancer incidence is very marked although there is general agreement that prostate cancer is the most 13.7%, 14.6%, and 22.4% reported in Kano [5], Jos [6] and Akwa Ibom [7] respectively. Regrettably, surgical specimens submitted to histopathology department for evaluation are dominated by specimens considered as likely to be malignant, a practice seen across all levels of care within Nigeria [7].…”
Section: Resultsmentioning
confidence: 99%
“…In Nigerian studies, the heterogeneity in cancer incidence is very marked although there is general agreement that prostate cancer is the most 13.7%, 14.6%, and 22.4% reported in Kano [5], Jos [6] and Akwa Ibom [7] respectively. Regrettably, surgical specimens submitted to histopathology department for evaluation are dominated by specimens considered as likely to be malignant, a practice seen across all levels of care within Nigeria [7]. There is need to continually educate the clinician on the need to send all resected specimen to surgical pathology laboratory for histopathological evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Suspicion or monitoring of bladder cancer is the main indication of UC, and however in Uyo, where this study was done, bladder cancer has been observed to be a rare tumor such that in a previous Uyo cancer study, it was not listed. [ 12 ] This may be the reason for the small sample size.…”
Section: Discussionmentioning
confidence: 99%